Realizing Scale in Smallholder-Based Agriculture : Policy Options for the Philippines - World Bank (World Bank, Washington, DC, 2021)
In recent decades, the agriculture and fisheries sector in the Philippines has grown but has clearly not lived up to its potential. Philippine agriculture has weathered the impact of the Coronavirus (COVID-19) pandemic better than the overall national economy. Recent government reports highlight the difficulty of modernizing Philippine agriculture under circumstances in which farmland is continuously fragmented, institutional arrangements for farm-to-market coordination and distribution are underdeveloped, and large parts of the food economy experience significant logistical bottlenecks and costs. This report combines results from three activities undertaken from mid-2020 to the first months of 2021. This report has five chapters. Chapter 2 reviews recent policy developments and some current priorities of the Department of Agriculture (DA). Chapter 3 describes the spatial analysis, highlighting the differences in agriculture’s transformative potential in different regions of the country. Given that spatial strategies are a relatively new departure in Philippine agriculture, Chapter 4 draws on experience at the national and subnational levels of other Asian countries to derive positive lessons for implementing them in the Philippines.